A co-operative business approach in a values-based supply chain: A case study of a beef co-operative. Issue 2 (December 2017) - Hooks, T.; McCarthy, O.; Power, C.; Macken-Walsh, Á.
Highlights: The industrialisation of the agri-food sector has enabled power imbalances to emerge in the supply chain that tend to disfavour farmers and are a key threat to family farm viability. Farmers have utilised co-operatives to redress these power imbalances and enhance viability and more recently, values-based supply chains (VBSCs) to promote values of equity, sustainability, fair pricing and transparency, mirroring the values of co-operatives. This paper aimed to understand, from members' perspectives, how the theoretical 'fit' between co-operatives and VBSC's translates in practice, focusing on the central role and importance of co-operative members. Findings indicated that responsiveness of the beef co-operative to customer preferences within the chain supported dynamics where chain partners exerted significant influence over internal co-operative functions, threatening its sustainability. While VBSCs and co-operatives share many principles and ambitions, co-operative success is dependent on balancing relationships and maintaining co-operative values. Abstract: The industrialisation of the agri-food sector has enabled power imbalances to emerge in the supply chain that tend to disfavour farmers. Exposure to price volatility, stemming from these power imbalances, is a key threat to family farm viability. Farmers have utilised co-operatives to redress these power imbalances and enhance viability. Separately, values-based supply chains (VBSCs) have emerged as an alternative to commodity-based supply chains, embodying values of sustainability, equity, fair pricing and transparency. Similarly, co-operatives embody these values and are adaptable business models that represent a good fit for integration to VBSCs. A qualitative case-study of a beef cooperative, integrated to a VBSC, is presented. This aimed to understand, from members' perspectives, how the theoretical 'fit' between cooperatives and VBSC's translates in practice, focusing on the central role and importance of co-operative members. VBSCs and co-operatives aim to promote fair and equitable governance structures. However, findings indicated that responsiveness of the beef co-operative to customer preferences supported dynamics where non-member partners exerted significant influence over internal co-operative functions. This, in turn, had implications for the co-operative and threatened its sustainability. While VBSCs and co-operatives share many principles and ambitions, co-operative success is dependent on balancing relationships and maintaining co-operative values.